Modelling groundwater aquifer to estimate water sustainability in Sana’a basin / Izzadin Ali Ahmed Al-Shaez - Al-Shaez, Izzadin Ali Ahmed (Institute of Graduate Studies, 2017)
Escalating water scarcity threatens global sustainable development. Water scarce regions will increase worldwide during the current century, as the water demand rate is more than twice the population growth rate. Yemen has one of the fast growing population rates in the world and is facing high water stress. Sana’a city, in particular, is experiencing a critical water shortage due to industrialisation, urbanisation and fast population growth rate. The water table at Sana’a aquifer, which is a groundwater-dependent city, has dropped significantly since 1972, as new technology was introduced to extract groundwater. Some studies estimated that Sana’a city would be the first metropolitan area to run dry during the coming few decades due to unsustainable groundwater pumping, as many wells will be depleted. This dissertation’s main aim is to evaluate the impact of climate change on groundwater resource in the Sana’a basin aquifer. To achieve the objectives of the study, firstly, the total groundwater recharge amount and spatial distribution were estimated using chloride mass balance. Selected wells and locations were chosen to collect groundwater and rainfall samples. In total, 22 sites spread all over the basin were chosen and the samples were collected during the two rain seasons from March-May and July-August in the year 2014. Likewise, 22 wells covering all the basin area were chosen to take groundwater samples for the chloride concentration test. The samples were taken during the rain season from March-May and July-August in 2014. After that, a chloride content analysis was carried out in the laboratory. The samples were collected and transported according to the standard procedure under the chemistry laboratory specified conditions. The results indicate that the overall recharge rate is almost 6.3% of the annual rainfall.